Landscape architecture and gender - Smit, Fi (School of Architecture, Planning and Geomatics, 2018)
This Dissertation Project is concerned with the meeting of Gender and Landscape Architectural theory, and aims to populate this (as yet) rare interface that requires urgent attention in discourse and practice. The Study is a research paper supporting the Dissertation Project by locating landscape architecture within the discourse on gender, and draws on Cultural Geography, Sociology, Intersectional, De-colonial and Feminist theory to argue that spatial design and the fields that engage with the production of public open space are key in understanding and addressing gender inequality. This is important because the gendered reproduction of space (and specifically, landscape) has tangible and pervasive effects on the access to, activity in, and safety of our public realm. Landscape positionality, the Nature/Culture dualism, Ecofeminism and Landscape theory are aligned in this Study, that engages with a topic that warrants a great deal of further research and development. The gendered experience, most often taking the form of various manifestations of rape culture, is particularly severe and restrictive in South Africa. Public open space is especially important to the struggle for equality and recognition across the hierarchies of privilege and power that stratify our society. Due to the unique intersections of violent constructions of masculinity, heteronormative and cisnormative socio-cultural codes, patriarchal social order, racial and racialised spatial and economic inequality and rape culture, women and gender minorities' movement, autonomy and potentials are severely limited. These spatial realities and socio-cultural inequalities are experienced every day, and they are gaining increased attention worldwide as social movements that include LGBTQI rights, the #MeToo Campaign, 16Days of Activism Against Gender-based Violence bring the power and privilege of intersecting systems of oppression to light, where they can be understood, undermined, transformed and dismantled. Fear and the socio-cultural reproductions of the spatial exclusions that patriarchy imposes upon those it "others", is studied through the interviewing of participants about their perceptions of safety, access and activity in public open space. The Study also gives attention to the dearth of landscape architectural theory that recognises gender as a fundamental informant in the practice and theory of the landscape architectural profession. Feminist Landscape architectural theorists are few and far between, and the study argues that the last 50 years of development in the field has functioned in service of the dominant socio-cultural paradigms by knowingly or unknowingly excluding the extremely relevant advances in the fields mentioned above. By polarising the understandings of 'sustainability' and 'ecology' away from the deeply interrelated realms of sociology, philosophy, cultural geography and anthropology, the construction of Landscape architecture as a profession loses its ideological soul - humans. Whether we like it or not, we are architects and designers of spatial realities - both tangible and intangible, as landscape is not just physical elements, but also 'paysage'. As architects we design with nature for the sake and benefit of the whole. And that whole includes homo sapiens - our processes are natural processes, our artefacts are no less valid in Nature than the weathering of a mountain into stones and sand. The distinct forms and the experiences curated within landscape architectural artefacts evoke not only emotional response, but have the ability to transcribe attitudes. What then, is gender-conscious landscape architecture? The Enquiry phase answers this question by using Cristophe Girot's Trace Concepts (Landing, Grounding, Finding) to engage with a process. The literature shows that feminist architecture and landscape architecture is not a style, but a kind of activity - deeply dependent on the agenda that the designer must be constantly aware of - dependent on positionality. There are rather "…feminist ways of looking at and making architecture, but these are based on a certain approach, not a 'recipe'. This approach stems initially from an understanding that our surroundings are not neutral, that there is a relationship between the content of architecture and our … social structure. The Enquiry phase recognizes this way of knowing as a complex and reflexive condition that includes consideration of a multitude of factors, to approach a design with a gender-sensitive lens is to include a much wider range of considerations than gender alone. Attention to the cultural reproduction of space by virtue of a sensitivity to proxemics, by embracing subjectivity as a design strategy, by embarking on site analysis that involves much more that one view or the layering activity from one vantage point (thereby avoiding the danger of a single story) characterises the enquiry phase, that was continuously informed by the theoretical underpinnings of the Study which was written simultaneously. Enquiry involves the grounding of the design process in a site, and the Tafelberg road is chosen for its positionality and unique patterns of use. This site is visited periodically, documented, experienced, consulted and slowly revealed to be a landscape physically and ideologically continuous with its various contexts - geomorphic, historic, ecological, hydrological etc.. The Founding phase has no discernable beginning point, as it includes the spatialisation of the conceptual development in both written/drawn and idea/ imagery form. It involves spatial investigations in model-making, revisiting the site to test ideas, spatial imaginings and experiential design that is guided by concepts such as Contextualising, Sequencing, Conceal and Reveal, Pause and Program and Opening.